Fuzzy soft Gamma-ring - (:unkn) unknown (SHIRAZ UNIV, 2012)
The concept of fuzzy soft Gamma-ring is introduced; and some properties of fuzzy soft Gamma-rings are given. Then the definitions of fuzzy soft Gamma-ideals are proposed and some of their theories are considered.
Keywords: Gamma - ring; fuzzy soft ring; soft ring; BCK/BCI-ALGEBRAS; SET-THEORY; IDEALS